Exploring interdisciplinary nursing care models: A Qualitative Clinical Study - Anita Lontaan; Yohan Trayanus Lasarus Djaha (Edukasi Ilmiah Indonesia, 2026)
Introduction: The increasing complexity in healthcare systems demands integrated, collaborative approaches to patient care. Interdisciplinary nursing care models have been promoted to enhance care coordination, patient safety, and quality outcomes. However, limited qualitative evidence exists regarding how these models are understood, implemented, and experienced by nurses in clinical practice. This study aimed to explore interdisciplinary nursing care models from nurses’ perspectives, focusing on roles, communication processes, facilitators, barriers, and perceived impacts on patient care and professional development. Methods: A qualitative clinical study was conducted in selected clinical units of a tertiary healthcare facility. Purposive sampling was used to recruit registered nurses with at least one year of clinical experience and active involvement in interdisciplinary care. Data were collected through semi-structured, in-depth interviews and analyzed using thematic analysis. Trustworthiness was ensured through member checking, audit trails, and reflexive practices. Results: Seven major themes emerged: understanding of interdisciplinary nursing care, nurses’ roles and responsibilities, communication and collaboration, facilitators of interdisciplinary care, barriers to interdisciplinary care, impact on patient care outcomes, and professional development and learning. Effective communication and collaboration were identified as the most critical elements supporting interdisciplinary care. Nurses played central roles as care coordinators, contributing to improved care quality, patient safety, and patient-centered outcomes. Organizational support and mutual respect facilitated collaboration, while hierarchical structures, role ambiguity, and workload constraints were identified as key barriers. Conclusion: Interdisciplinary nursing care models are strongly influenced by communication quality, recognition of nurses’ professional roles, and organizational support. Despite existing barriers, effective interdisciplinary collaboration enhances patient outcomes and supports continuous professional development. Strengthening structured interprofessional communication and supportive organizational policies is essential for sustainable interdisciplinary nursing practice.